Case report: Concurrent pylephlebitis and subarachnoid hemorrhage in an octogenarian patient with Escherichia coli sepsis - Zhao, Yong; Feng, Dandan; Wang, Xinyu; Sun, Yuanyuan; Liu, Junni; Li, Xiaodong; Zhou, Nannan; Wang, Jianchun (Frontiers in Medicine, 2023)
Background: Pylephlebitis refers to an infective suppurative thrombosis that occurs in the portal vein and its branches. Concurrent pylephlebitis and subarachnoid hemorrhage (SAH) are rare but fatal for patients with sepsis. This scenario drives the clinicians into a dilemma of how to deal with coagulation and bleeding simultaneously. Case summary: An 86-year-old man was admitted to hospital for chills and fever. After admission, he developed headache and abdominal distension. Neck stiffness, Kernig's and Brudzinski's sign were present. Laboratory tests discovered decreased platelet count, elevated inflammatory parameters, aggravated transaminitis, and acute kidney injury. Escherichia coli (E. coli) were identified in blood culture. Computed tomography (CT) revealed thrombosis in the superior mesenteric vein and portal veins. Lumbar puncture and Brain CT indicated SAH. The patient had eaten cooked oysters prior to illness. It was speculated that the debris from oyster shell might have injured his intestinal mucosa and resulted in bacterial embolus and secondary thrombosis in portal veins. The patient was treated with effective antibiotics, fluid resuscitation, and anticoagulation. The dose titration of low molecular weight heparin (LMWH) under close monitoring attributed to diminution of the thrombosis and absorption of SAH. He recovered and was discharged after 33-day treatment. One-year follow-up indicated that the post-discharge course was uneventful. Conclusions: This report describes a case of an octogenarian with E. coli septicemia who survived from concurrent pylephlebitis and SAH along with multiple organ dysfunction syndrome. For such patients with life-threatening complications, even in the acute stage of SAH, decisive employment of LMWH is essential to resolve thrombosis and confers a favorable prognosis.